Millennials rising : the next great generation / by Neil Howe and Bill Strauss ; cartoons by R.J. Matson - Howe, Neil; Strauss, William (New York : Vintage Books, 2000)
'In this remarkable account, certain to stir the interest of educators, counselors, parents, and people in all types of business as well as young people themselves, Neil Howe and William Strauss introduce the nation to a powerful new generation: the Millennials. They will also explain: Why today's teens are smart, well-behaved, and optimisitc, and why you won't hear older people say that. Why they get along so well with their Boomer and Xer parents. Why Millennial collegians will bring a new youth revolution to America's campuses. Why names like "Generation Y" and "Echo Boom" just don't work for today's kids. Having looked at oceans of data, taken their own polls, and talked to hundreds of kids, parents, and teachers, Howe and Strauss explain how Millennials are turning out to be so dramatically different from Xers and boomers and how, in time, they will become the next great generation.' From publisher's description
The next great generation -- From babies on board to power teens -- The coming millennial revolution -- The baby boomlet (demography) -- Kinderpolitics (political economy) -- Ground zero of the culture wars (family) -- Raising standards for regular kids (school) -- Jiggy with it (pace of life) -- Zero tolerance (conduct) -- Junior citizens (community) -- The happiness business (culture) -- Rocket cash (commerce) -- Planet pokemon (world) -- The clock is tickin' -- Hero generations in history -- A capacity for greatness -- Millennials rising
Includes bibliographical references
Keywords: Youth -- United States